Acute diethyl nitrosamine and cadmium co‐exposure exacerbates deficits in endocrine balance, sperm characteristics and antioxidant defence mechanisms in testes of pubertal rats (2019)
Diethylnitrosamine (DEN) and cadmium are environmental contaminants of known poisonous consequences in animals and humans. We examined the influence of acute oral co‐exposure to DEN (10 mg/kg) and cadmium (5 mg/kg) on endocrine balance, semen and antioxidant status in rat testes. The results indicated decreases (p < 0.05) in the weight of the testis and organo‐somatic index of the testes in rats administered with either DEN or cadmium were aggravated in the co‐exposed rats. Serum concentrations of follicle‐stimulating hormone (FSH), luteinising hormone (LH) and testosterone decreased, and were more pronounced in rats co‐treated with DEN and cadmium. Enzymatic and non-enzymatic antioxidant activities decreased following separate exposure to DEN and cadmium, and were increased in rats co‐treated with DEN and cadmium. The significant (p < 0.05) increases in malondialdehyde (MDA) was complemented by marked increase in sperm abnormalities, reduction in the sperm count, motility and viability compared with control. Histologically, co‐exposure to DEN and cadmium aggravates their discrete effects on the testes. Co‐exposure to DEN and cadmium elicited more severe endocrine disruption and testicular oxidative damage in rats, revealing additive adverse effects on testicular functions in rats and as such, may put exposed individual at greater risk.